Analisis dan Perancangan Perbaikan Sistem Manajemen Pergudangan - Andri Ikhwana; Dewi Rahmawati; Viona Iswi Nurlestari (Jurnal Kalibrasi, 2022)
The warehousing management system is one of the supporting factors for improving company performance through structuring the existing warehousing system at the company. The warehousing system includes how to store goods in the warehouse which must be accompanied by standard operating procedures so that every activity in the warehouse is better. The purpose of this study was to identify problems in warehousing activities accompanied by standard operating procedures for handling goods in the warehouse. This study uses a descriptive qualitative approach through distributing questionnaires supported by the results of interviews with the warehouse manager. The approach to identifying problems in the warehouse is by using a fishbone diagram and designing a warehouse management system improvement by designing a standard operating procedure for storing goods. The results of the study found that problems arise due to various factors including the condition of the workers, the warehouse environment, the method of handling goods in the warehouse and the type of material that is the object stored in the warehouse. Based on these problems, efforts are needed to improve the warehousing management system through the design of standard operating procedures for storing goods as guidelines or rules in carrying out warehousing activities. To support improvements in the arrangement of the warehouse management system, it is better to focus on the design of a standard operating system for storing goods in warehouses.